Teoresi Teologica - Mario Gennari (Firenze University Press, 2019)
The article focuses on the connection between what is theoreticus and what is theologicus. If the theoresis consists of a theoretical thought that makes human being capable of reaching the highest level of his thought about theos and then proceeding towards the knowledge of the world and human being, the possibility of a Theological Theoresis concerns the theological Being also in its relations with metaphysics and ontology. Thinking theoretically - therefore philosophically - of theos recalls the dimensions of the mystery, of the eternal and of the sacred in respect of a negative theology, also evoking the Welttheologie - the world theology - characterized by an authentic spirit of religiosity.